Outcomes and Experiences of Child-Bearing Women with Nasopharyngeal Carcinoma - Ma L; Chen F; Kong X; Xu T; Fei Z; Fang W; Wang B; Wu H (Cancer Management and Research, 2020)
Liqin Ma,1,* Fei Chen,2,* Xiangquan Kong,3,* Ting Xu,2 Zhaodong Fei,1 Weining Fang,1 Binyi Wang,1 Haixia Wu2 1Department of Radiation Oncology, Fujian Cancer Hospital and Fujian Medical University Cancer Hospital, Fuzhou, People’s Republic of China; 2Fujian Medical University, Fuzhou, People’s Republic of China; 3Department of Radiation Oncology, Fujian Medical University Affiliated Xiamen Humanity Hospital, Fuzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Liqin MaDepartment of Radiation Oncology, Fujian Cancer Hospital and Fujian Medical University Cancer Hospital, No. 420, Fuma Road, Fuzhou, Fujian 350014, People’s Republic of ChinaTel +8613609537603Fax +86 591-83660063Email maliqin3@126.comPurpose: Nasopharyngeal carcinoma (NPC) is more common among women in Southeast Asia. An important issue is whether it is safe for them to bear children after treatment and when it is safe to do so. We conducted this study to explore the relation between fertility and prognosis in child-bearing women with NPC.Patients and Methods: Child-bearing women were defined as young women between the ages of 18 and 30. A total of 127 eligible child-bearing NPC patients were identified from December 2003 to December 2014. The patients were divided into two groups, depending on whether or not they had post-therapeutic births. The Kaplan–Meier method was used for survival analyses. The Log rank test was used to compare two survival curves and the independent significances of different prognostic factors were assessed by Cox proportional hazards regression analysis.Results: The 5-year overall survival (OS) and disease-free survival (DFS) in the Childbirth group were significantly higher than those in the Non-Childbirth group (100% vs 88.8%, P = 0.026 and 100% vs 77.5%, P = 0.007, respectively). In the Childbirth group, no difference was found in the 5-year DFS between different birth interval times, from 1 to 5 years after treatment. The clinical stage was identified as the risk factor of OS (HR = 101.725, 95% CI: 2.160– 4790.910, P = 0.019), and consequent childbirth after treatment was associated with favorable DFS (HR = 0.148, 95% CI: 0.034– 0.643, P = 0.011).Conclusion: Post-therapeutic birth did not increase the mortality risk of child-bearing women with NPC. There was no significant correlation between the subsequent birth time window after treatment and the prognosis.Keywords: nasopharyngeal carcinoma, fertility, child-bearing mortality risk, post-treatment